UNOCCUPIED ELECTRONIC STATES OF EPITAXIAL IRON LAYERS ON CU(100) - Fauster, Thomas; et al. (Zeitschrift für Physik B Condensed Matter, 1992)
Inverse photoemission spectra were taken for thin epitaxial iron films on Cu(100). For a film thickness of eight monolayers the observed electronic states are characteristic for a fcc(100) surface. The d-bands of iron show a ferromagnetic exchange splitting of 1.1 eV, considerably smaller than the bulk value of 1.8 eV, which we observe for film thicknesses above 18 monolayers.